+0

# long Operations AKA B.E.D.M.A.S.

0
190
4

Hello I am having lots off problems with this equation

(-3+2x(7- -5))x(-8-2x(-6+3))

Guest Oct 4, 2017
edited by Guest  Oct 4, 2017

#3
+6615
+2

Remember that this isn't called an "equation" since we are not given an equal sign.

This is called an "expression."

(-3 + 2 × (7 - -5) ) × ( -8 - 2 × (-6 + 3) )     First, do the addition inside the innermost parenthesees.

7 - -5  =  7 + 5  =  12     and     -6 + 3  =  -3

=  (-3 + 2 × 12 ) × ( -8 - 2 × -3 )

=  (-3 + 2 × 12 ) × ( -8 - 2 × -3 )         Next, we must work inside the remaining parenthesees.

=  (-3 + 24 ) × ( -8 - -6 )

=  (-3 + 24 ) × ( -8 - -6 )      Now do the addition inside of the remaining parenthesees.

-3 + 24  =  24 - 3  =  21     and     -8 - -6  =  -8 + 6  =  -2

=  21 × -2

Finally, multiply these together.

=  -42

hectictar  Oct 4, 2017
edited by hectictar  Oct 4, 2017
Sort:

#1
0

what do you mean by "equations"?

P.S. Im a middle schooler (7th grade) and this problem is pretty easy to solve for me (no offence)

Guest Oct 4, 2017
#2
0

I mean long equations!!

.

.

.

lol

Guest Oct 4, 2017
#3
+6615
+2

Remember that this isn't called an "equation" since we are not given an equal sign.

This is called an "expression."

(-3 + 2 × (7 - -5) ) × ( -8 - 2 × (-6 + 3) )     First, do the addition inside the innermost parenthesees.

7 - -5  =  7 + 5  =  12     and     -6 + 3  =  -3

=  (-3 + 2 × 12 ) × ( -8 - 2 × -3 )

=  (-3 + 2 × 12 ) × ( -8 - 2 × -3 )         Next, we must work inside the remaining parenthesees.

=  (-3 + 24 ) × ( -8 - -6 )

=  (-3 + 24 ) × ( -8 - -6 )      Now do the addition inside of the remaining parenthesees.

-3 + 24  =  24 - 3  =  21     and     -8 - -6  =  -8 + 6  =  -2

=  21 × -2

Finally, multiply these together.

=  -42

hectictar  Oct 4, 2017
edited by hectictar  Oct 4, 2017
#4
+1

Thank you!

Guest Oct 4, 2017

### 19 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details